Brand Awareness and Brand Association in Continuing Studies at Open and Distance Higher Education - Sediyaningsih, Sri; Rachman, Ace Sriati; Ardiasih, Lidwina Sri; Wiradharma, Gunawan; Arisanty, Melisa (Jurnal Ilmu Komunikasi, 2023)
Distance Education has great potential to become a model for the world's future education. The rapid development of technology, the demands of the global professional world, as well as various extraordinary events, such as the COVID-19 pandemic which could recur at any time, are the main reasons for the need to implement distance education. Therefore, to maintain the existence of distance education, research is needed that can look at perceptions of brand equity, namely brand awareness and brand association with perceived quality. This research aims to explain how society accepts open and distance state colleges, particularly among students in Indonesia. The research subjects were 812 respondents obtained through probability sampling using multistage random sampling from three regions in Indonesia, namely Vocational High School Bina Warga Bandung representing western Indonesia, Public High School 16 Makassar representing Central Indonesia, and Public High School 1 Jayapura representing the eastern part of Indonesia. The results of the research show that there is a strong relationship between brand awareness and community brand association on the desire to continue studying at open and distance higher education institutions. This research providing recommendations for PTJJ should not only focus on promotion/marketing strategies to increase interest in continuing community studies at PTJJ but also focus on strategies that can increase brand equity.